Emergency and Critical Care of Ferrets - Orcutt, Connie J. (Vet Clin North Am Exot Anim Pract, 1998)
Ferrets are becoming increasingly popular as pets in the United States. Emergency situations involving ferrets are most often caused by gastrointestinal disease, neoplasia, cardiac disease, or endocrinopathy. Hospitalization and supportive care of the critically ill ferret, emergency treatment techniques, and diagnostic procedures are discussed. Diseases most commonly involved in critical presentations are reviewed along with treatment protocols.